PENGGUNAAN APLIKASI EVALUASI BERBASIS QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATERI EKONOMI KREATIF DI SMK NEGERI 1 KOTA SERANG - Siti Khodijah; Dewi Surani; Iip Rifa'i; Namiroh (Cakrawala Pedagogik, 2023)
The purpose of this study was to determine the use of the quizizz application on students' learning motivation. After application, whether it has increased or not. The research method used by researchers is qualitative method, where information is taken directly from the field. Data collection was carried out by distributing questionnaires, interviews and documentation. The subjects of this research were students of SMK Negeri 1 Kota Serang class X DKV 1, with a sample of 38 students, using a purposive sampling technique. While the object of research is motivation in using quizizz-based evaluation applications. Based on the results of the questionnaire data, all of the responses strongly agreed and agreed to get 67.2% indicating that the use of Quizizz was very effective in increasing student learning motivation and the interviews conducted showed that students were motivated to learn when knowing the value that appears in the Quizizz application after being played makes students to study harder to follow the evaluation. The conclusion of this study is that the quizizz application is very good to use to create learning motivation in conducting each evaluation. This research provides a discourse for teachers to be able to use quiziz as an alternative medium to find out learning outcomes.